Identificação e quantificação molecular de Bacillus methylotrophicus em raízes de soja - Silva, Adriane das Graças (2021)
Soybean (Glycine max) is the main agricultural crop in Brazil, which is one of the world's largest exporters of this grain. However, soybean productivity is injured by diseases triggered by pathogens, nematodes and pests. The endospore-forming gram-positive bacteria Bacillus methylotrophicus is defined as a biocontrol agent (BCA), because this rhizobacteria produces metabolites with antibiotic activity, especially against nematodes found in root plants. The management strategies of these phytoparasites involve the concomitant use of products based on different microorganisms species. However, due to the complexity of rhizosphere environment, is challenging to predict the individual performance of these agents. Therefore, the present study aimed identify and quantify, through molecular assays, strains of B. methylotrophicus in soybean roots. Through in silico analysis genes of this strain were aligned with genes of other Bacillus strains to predict single nucleotide polymorphisms (SNPs) regions. For species discrimination, genes encoding the enzyme methylthioribulose-1-phosphate dehydratase (MtnB) and spore germination protein GerkB (GerkB) were selected as probable quantitative markers, since that two subsequent SNPs in region 3 ' of primer alignment were identified. The specificity of primers was validated by conventional PCR and two primers combinations for the MtnB gene able to discriminate B. methylotrophicus from other species with strict phylogenetic relationship was selected. Primer combination 1 (C1) was used to construct the absolute standard curve for B. methylotrophicus DNA quantification from soybean roots with treatments with different BCAs species. The qPCR analyzes showed that the highest DNA recovery of the bacteria of interest was obtained from the experiments with B. methylotrophicus + B. subtlis, followed by B. methylotrophicus + B. subtilis + Trichoderma asperellum. B. methylotrophicus DNA was not recovered from untreated controls (UTC) and there was no statistical difference between UTC and treatment with only B. methylotrophicus. Therefore, the molecular marker used in this study is specific to B. methylotrophicus and can be used to infer the influence of other BCAs on development of B. methylotrophicus.